Interactions of the influences of habitat protection, habitat heterogeneity, and periodic flooding on waterbirds of the lower Paraná River, Argentina. (29th April 2021) - Quiroga, Virginia M.; Ronchi‐Virgolini, Ana Laura; Lorenzón, Rodrigo E.; Lammertink, Martjan
Abstract: How waterbirds respond to environmental characteristics of river systems is of interest because of the high biodiversity of waterbirds in these systems, their ecological roles, and the importance of waterbirds in hunting for sport or sustenance. We studied the influence of natural factors (water‐level fluctuations and environmental heterogeneity) and human‐related factors (habitat protection, which primarily excludes cattle grazing and hunting) on waterbirds in the Pre‐Delta region of the Paraná River system during three years. Our objectives were to evaluate the environmental factors that influence the assemblages of waterbirds and whether these variables explain differences in waterbird assemblages between protected and non‐protected areas. Both species richness and abundance of waterbirds per point count increased with the diversity of land cover categories at count spots. Species richness also increased with the surface of open water. The larger surface of open water in the non‐protected area contributed to explaining the higher species richness and abundance of waterbirds, including species with hunting pressure, in this area. During floods, the protected area maintained a high abundance of waterbirds, probably because the higher proportion of trees and aquatic vegetation in this area provided perches and foraging sites. We recommend enlarging protected areas in the Pre‐Delta region because of their role of sheltering waterbirds during floods. Protected and non‐protected areas serve complementary functions in providing habitat for waterbirds; therefore, it is important to maintain both of these management types in the landscape. Abstract in Spanish is available with online material. Abstract : We studied the influence of natural factors (water level fluctuations and environmental heterogeneity) and human‐related factors (habitat protection, which primarily excludes cattle grazing and hunting) on waterbirds in the Pre‐Delta. The larger surface of open water in the non‐protected area contributed to explaining the higher species richness and abundance of waterbirds, including of species with hunting pressure, in this area. During floods, the protected area maintained a high abundance of waterbirds, probably because the higher proportion of trees and aquatic vegetation in this area provided perches and foraging sites. protected and non‐protected areas serve complementary functions in providing habitat for waterbirds; therefore, it is important to maintain both of these management types in the landscape. RESUMEN: La forma en que las aves responden a las características ambientales de los sistemas fluviales es interesante debido a la alta biodiversidad, las funciones ecológicas y la importancia en la caza por deporte o sustento de las aves acuáticas en estos sistemas. Estudiamos la influencia de factores naturales (fluctuaciones del nivel del agua y heterogeneidad ambiental) y antrópicos (protección del hábitat, que excluye principalmente el pastoreo de ganado y la caza) en las aves acuáticas en la región Pre‐Delta del sistema del río Paraná durante tres años. Nuestros objetivos fueron evaluar cuáles son los principales factores ambientales que influyen en los ensambles de aves acuáticas y si estas variables explican las diferencias en los ensambles de aves acuáticas entre áreas protegidas y no protegidas. La riqueza de especies y la abundancia de aves acuáticas por punto se incrementaron con la diversidad de categorías de coberturas de suelo. La riqueza de especies también aumentó con la superficie de aguas abiertas. La mayor superficie de aguas abiertas en el Área no protegida contribuyó a explicar la mayor riqueza de especies y abundancia de aves acuáticas, incluidas las especies con presión de caza, en esta área. Durante las inundaciones, el Área Protegida mantuvo una gran abundancia de aves acuáticas, probablemente porque la mayor proporción de árboles y vegetación acuática en esta área proporcionaba perchas y sitios de alimentación. Recomendamos ampliar las áreas protegidas en la región Pre‐Delta debido a su papel de albergar a las aves acuáticas durante las inundaciones. Nuestros resultados sugirieron que tanto las áreas protegidas como no‐protegidas cumplen funciones complementarias como hábitat para las aves acuáticas; así, es importante mantener ambos tipos de manejo en el paisaje.